Non-pharmacological therapies for treating non-motor symptoms in patients with Parkinson’s disease: a systematic review and meta-analysis - Zhang, Yu; Liu, Shuang; Xu, Ke; Zhou, Yan; Shen, Yiwei; Liu, Zhengnan; Bai, Yan; Wang, Shun (Frontiers in Aging Neuroscience, 2024)
Objective The non-motor symptoms of Parkinson’s disease (PD) are an important part of PD. In recent years, more and more non-drug interventions have been applied to alleviate the non-motor symptoms of PD, but the relevant evidence is limited. This systematic review and meta-analysis was designed to evaluate the efficacy of non-drug interventions in patients with non-motor symptoms in patients with PD. Methods Seven databases, including Pubmed, Embease, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang database (WANFANG), VIP database (VIP), and China Biomedical Literature Service System (CBM) were searched from the establishment of the database to December 2023. Non-drug interventions such as acupuncture, cognitive behavioral therapy (CBT), exercise, repetitive transcranial magnetic stimulation (rTMS), and non-motor symptoms of Parkinson’s disease were selected as search words, and two independent evaluators evaluated the included literature’s bias risk and data extraction. The therapeutic efficacy was evaluated by the Parkinson’s Disease Sleep Scale (PDSS), Hamilton Depression Scale (HAMD), Beck Depression Inventory (BDI), Hamilton Anxiety Scale (HAMA), Montreal Cognitive Assessment (MoCA), Minimum Mental State Examination (MMSE), and Parkinson’s Disease Questionnaire-39 (PDQ-39). RevMan 5.4.1 (Reviewer Manager Software 5.4.1). Cochrane Collaboration, Oxford, United Kingdom analyzed the data and estimated the average effect and the 95% confidence interval (CI). A heterogeneity test is used to assess differences in the efficacy of different non-drug treatments. Results We selected 36 from 4,027 articles to participate in this meta-analysis, involving 2,158 participants. Our combined results show that: PDSS: [mean difference (MD) = −19.35, 95% CI (−30.4 to −8.28), p < 0.0006]; HAMD: [MD = −2.98, 95% CI (−4.29 to −1.67), p < 0.00001]; BDI: [MD = −2.69, 95% CI (−4.24 to 4.80), p = 0.006]; HAMA: [MD = -2.00, 95% CI (−2.83 to −1.17), p < 0.00001]; MMSE: [MD = 1.20, 95% CI (0.71 to 1.68), p < 0.00001]; CoMA: [MD = 2.10, 95% CI (−0.97 to 3.23), p = 0.0003]; PDQ-39: [MD = −4.03, 95% CI (−5.96 to −1.57), p < 0.00001]. Conclusion The four non-drug measures used in our review showed significant improvements in sleep, depression, anxiety, cognition, constipation, and quality of life compared with the control group, and no serious adverse events were reported in the included research evidence, and we found that there were some differences among the subgroups of different intervention methods, but due to the less literature included in the subgroup, and the comparison was more indirect. So, we should interpret these results carefully. Systematic review registration www.crd.york.ac.uk/PROSPERO, identifier CRD42023486897.